PENGARUH KUALITAS PELAYANAN DAN SUASANA KAFE TERHADAP KEPUASAN KONSUMEN PADA KAFE PONDOK DPR KOTA SIBUHUAN - ,, Yuliandari; Heriyanto, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research is aimed at analyzing the impact of service quality and the café atmosphere on consumer satisfaction at Kafe Pondok DPR Kota Sibuhuan, both partially and simultaneously. The method used in this research is a quantitative approach with data collection through the distribution of questionnaires to 99 respondents who are consumers of Kafe Pondok DPR Kota Sibuhuan. The sampling technique used is accidental sampling. Data processing was carried out using SPSS software version 22.0. The analysis results show that service quality has a significant impact on customer satisfaction. Additionally, the café's ambiance also proves to have a significant effect on customer satisfaction. Simultaneously, both variables, namely service quality and café ambiance, have a positive and significant impact on customer satisfaction at Kafe Pondok DPR Kota Sibuhuan. Keywords: service quality, café atmosphere, customer satisfaction.